MULTICULTURAL EDUCATION IN THE PERSPECTIVE OF ISLAM NUSANTARA: A CRITICAL ANALYSIS OF ABDURRAHMAN WAHID’S THOUGHT - Kusuma, M. Witra; Dzuhry, Robi'ul; Aslamiah, Rabi'atul; Sabariah, Hayatun (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study examines Abdurrahman Wahid’s (Gus Dur) ideas on multicultural education and their relevance to Islamic education in Indonesia. Through a literature review of his writings and speeches, the research finds that Gus Dur promoted an inclusive, tolerant, and culturally grounded Islam known as Islam Nusantara. He emphasized that education should foster mutual respect, empathy, and peaceful coexistence across religious and cultural differences. His rejection of exclusivist interpretations and advocacy for local cultural integration position his thought as a strong foundation against intolerance and radicalism. Gus Dur’s ideas remain highly relevant for building a tolerant and humanistic Islamic education today. Penelitian ini mengkaji pemikiran Abdurrahman Wahid (Gus Dur) tentang pendidikan multikultural dan relevansinya bagi pendidikan Islam di Indonesia. Melalui studi pustaka atas tulisan dan pidatonya, ditemukan bahwa Gus Dur mengusung Islam inklusif dan toleran yang dikenal sebagai Islam Nusantara. Ia menekankan pentingnya pendidikan yang menumbuhkan sikap saling menghargai, empati, dan hidup damai dalam keberagaman. Penolakannya terhadap tafsir tunggal dan dukungannya terhadap budaya lokal menjadikan gagasannya relevan untuk melawan intoleransi dan radikalisme. Pemikiran Gus Dur menjadi landasan penting dalam membangun pendidikan Islam yang manusiawi dan toleran.